Off-flavor characterization in high-nutrient-load tilapia ponds in Northern Thailand - Pornpimol Pimolrat (2018)
© Published by Central Fisheries Research Institute (CFRI) Trabzon, Turkey. The purpose of this research was to determine the levels of odorous compounds (geosmin or 2-methylisoborneol (MIB) that potentially cause off-flavor problems in fish reared in integrated, high-nutrient-load ponds in northern Thailand. Water samples were collected from threetilapia ponds located in Chiangrai province, every month from May 2013 to May 2014. Geosmin and MIB were analyzed by gas chromatography-mass spectrometry. The physico-chemical parameters were determined using standard techniques. The concentration of geosmin in water samples ranged between 0.01 and 0.06 μg L < sup > -1 < /sup > , while that of MIB ranged between 0.09 and 0.11 μg L < sup > -1 < /sup > . The concentration of geosmin was positively correlated (r=0.84; P < 0.01) with the density of cyanobacteria and chlorophyll a (r=0.57; P < 0.01) in the water. The highest concentration of MIB (0.11 μg L < sup > -1 < /sup > ) was observed in October, and over all samples, concentrations were positively correlated (r=0.56; P < 0.01) with culture period but negatively correlated with light intensity (r=-0.39; P < 0.05). Seven genera of cyanobacteria were most frequently encountered, namely: Anabaena sp., Oscillatoria sp., Pseudanabaena sp., Lyngbya sp., Phormidium sp., Planktolyngbya sp. and Synchococcus sp. The detailed patterns of association found suggest that Anabaena sp. and Oscillatoria sp. were the biological origins of geosmin, whereas the source of MIB was Pseudanabaena sp.These findings are an important step towards the prediction, control and management of the off-flavor problem in tilapia culture in high-nutrientload ponds.